Genetic and biological analyses of a herpes simplex virus intertypic recombinant reduced specifically for neurovirulence. - Javier, R T (1987)
RS6 is a herpes simplex virus intertypic recombinant derived from type 1 strain 17 syn+ and type 2 strain HG52. With a 50% lethal dose of about 10(5) PFU after intracerebral inoculation of mice, RS6 was approximately 100,000 times less neurovirulent than either of its wild-type parental viruses were. When compared with strains 17 syn+ and HG52, RS6 replicated intermediately in primary mouse embryo fibroblasts in vitro at 38.5 degrees C (mouse temperature) and to wild-type peak titers in mouse feet in vivo. In contrast, following intracranial inoculation of mice, RS6 replicated significantly less well than did either of its parental viruses in brains. The genetic defect(s) responsible for the reduced neurovirulence of RS6 was stable after in vitro and in vivo serial passage, was not manifested as temperature-sensitive plaquing in vitro, and did not affect thymidine kinase expression. These data indicate that RS6 has a genetic defect(s) specifically affecting its ability to replicate in the mouse brain. Using marker rescue technologies, we increased the neurovirulence of RS6 and localized one genetic determinant(s) involved with the reduced neurovirulence of this agent to 0.72 to 0.87 map units (and, tentatively, to 0.79 to 0.83 map units) of the herpes simplex virus genome. When coupled with the work suggesting that thymidine kinase expression is essential for efficient replication in nerve tissues and earlier reports from this laboratory and others, the results presented in this study indicate that more than one herpes simplex virus gene is involved with neurovirulence.